Why Rome fell : decline and fall, or drift and change? - Arnheim, M. T. W. (Michael T. W.) (John Wiley & Sons, Inc., 2022)
Explore an insightful and original discussion of the causes of the fall of the Roman Empire In Why Rome Fell: Decline and Fall, or Drift and Change?, celebrated scholar of Roman history Dr. Michael Arnheim delivers a fascinating and robust exploration of the causes of and reasons for Rome's fall in the West. Steeped in applications of elite theory to the later Roman Empire, the author discusses several interconnected issues that influenced the decline of Rome, including monarchy, power structure, social mobility, religion, and the aristocratic ethos. Incisive comparisons of the situation in Rome to those in the Principate and the Byzantine Empire shed light on the relative lack of "indissoluble union and easy obedience" (in Gibbon's phrase) in the later Roman Empire. Instead, the book reveals the divided loyalties of a fractured society that characterized Rome in its later years. Why Rome Fell also includes: A thorough introduction to the transition from the ancient to the medieval world, including discussions of monarchy, Diocletian and his relationship to the aristocracy, and Constantine's reforms Comprehensive explorations of the rise of the Roman Christian empire and Constantine's role Practical discussions of conflicting theories of what caused the fall of the Roman empire, including the Pirenne thesis, the malaria hypothesis, Gibbon's 'decline and fall' theory, and the role played by religion An indispensable resource for students, scholars and the general reader with an inquiring mind about history, Why Rome Fell deserves a place on the bookshelves of anyone with an interest in a sophisticated and original take on historical continuity and change.